Usage of ChatGPT in Higher Education - Dragojević, Tamara; Turudić, Jovana (Studies in Teaching and Education, 2024)
The accelerated development of technology has led to the creation of the ChatGPT artificial intelligence model, which enables text generation based on user queries. Although it represents an innovation in the domain of artificial intelligence, this model has not yet been sufficiently explored through empirical studies. Therefore, research has been conducted to delve deeper into the perceptions and attitudes of students regarding the usage of ChatGPT in higher education, aiming to gain a better insight into their awareness, attitudes, and expectations regarding this model. The sample included 200 students from the University of Novi Sad, and the data were analyzed using the SPSS program and measures of descriptive statistics. The research results indicate that students extensively use ChatGPT for academic purposes, recognizing benefits such as time savings and personalized learning experiences. However, the results also indicate concerns among students regarding potential decreases in creativity and critical thinking, as well as risks to user privacy. Additionally, the majority of students lacked experience with educational workshops or courses focused on the usage of ChatGPT in an academic context. Based on these findings, it is concluded that there is a need for educating students about more efficient and responsible usage of ChatGPT in higher education. Furthermore, the importance of further research and development of resources is emphasized to provide students with adequate support and training regarding this technological tool.